CHARACTERISTICS OF PRONUNCIATION SEGMENTATION OF ALVEODENTAL PHONEME [tˤ] IN STUDENT READING TEST - Ghani, Yanfa Rizal; Al Farisi, Mohamad Zaka; Maulani, Hikmah (Universitas Islam Sumatera Utara (UISU), 2024)
This study examines the segmentation and pronunciation accuracy of the alveodental phoneme thāʾ [tˤ] in Arabic based on students' reading tests. By employing a qualitative descriptive method with a content analysis design, the research seeks to obtain detailed descriptive data in the form of words and images. The Praat application is used to measure sound frequency from various sound sources, ensuring precise and comprehensive analysis. The results indicate that students face significant challenges in correctly pronouncing the phoneme [tˤ], with frequent articulation errors. These pronunciation difficulties are attributed to several factors, including the phonetic differences between the students' native languages and Arabic, the inherent complexity of Arabic phonemes, and the influence of various dialects or accents the students may possess. This study highlights the critical need for a thorough understanding of phoneme properties and emphasizes the importance of consistent practice to improve pronunciation accuracy of [tˤ]. By addressing these issues, educators can better support students in mastering Arabic pronunciation, ultimately enhancing their overall language proficiency. The findings of this research contribute to the broader field of phonetics and language education, offering valuable insights for language teachers and learners alike.